Current status of Traditional Chinese Medicine external application in integrated pension and medical service of Traditional Chinese Medicine for the elderly (中医外治法在中医药医养结合养老服务中的应用现状) - DONG Shuo (董硕); HUANG Yanping (黄砚萍); FENG Xiaoxuan (冯晓璇); LI Jie (李洁); DUAN Yajing (段雅静); FENG Xinxin (封幸幸) (中西医结合护理)
I ncreasing attention has been paid to health condition of the elderly as the fast growth of the elderly population. The Traditional Chinese Medicine external application has advantages of easy-to-use and low cost, and is highly accepted among patients. This paper summarized the current status of Traditional Chinese Medicine external application, such as moxibustion, auricular acupoint pressing therapy and Chinese Herbal medicine footbath, in integrated pension and medical service of Traditional Chinese Medicine for the elderly, and provides reference for the establishment and practice of pension and medical service with Traditional Chinese Medicine techniques. (随着老龄化趋势加重, 老年人群的健康问题是社会关注的重点。中医外治法具有操作简便、医疗成本低等优势, 患者更易于接受。本文总结了在中医药医养结合养老服务中的应用现状, 包括艾灸、耳穴压豆、中药足浴等中医特色技术, 旨在为改善老年人生活状况, 提高生存质量, 为中医外治法与医养结合相结合的养老服务提供参考。)